New Highlanders in Traditional Out-migration Areas in the Alps - Roland Löffler; Michael Beismann; Judith Walder; Ernst Steinicke (Revue de Géographie Alpine)
According to the population and migration development on a municipal level in the Alps since the last decades, it has become obvious that the population gain that began in France in the 1980s has been expanding ever since towards the eastern parts of the Alps. In this study we illustrate the distribution of the newcomers in various distinctiveness such as re-migrants, second home owners, multi-dwelling residents, relationship-migrants, new highlanders, working migrants, but also locals who, within their community, stay in their second home over extended periods. The effect of this latest demographic trend in the Eastern Alps is exemplified by two case studies in Friuli: First, in the German speaking language pocket of Sauris (Zahre), the influence of especially Italian newcomers on the autochthonous population and its culture can be observed, besides various social and economic aspects. In addition, in eastern Friuli the ongoing revitalization of ghost towns is examined, which represents an extreme case of repopulation and hence the preservation of Alpine settlement areas.